ChemInform Abstract: Kinesin Spindle Protein (KSP) Inhibitors in Combination with Chemotherapeutic Agents for Cancer Therapy. Issue 52 (24th December 2013) - Song, Hualong; Zhou, Shanshan; Wang, Rubing; Li, Shaoshun
Abstract Review: 134 refs.